Remarkable Rituximab Response on Tremor Related to Acute‐Onset Chronic Inflammatory Demyelinating Polyradiculoneuropathy in an Antineurofascin155 Immunoglobulin G4–Seropositive Patient. Issue 5 (24th August 2018) - Demichelis, Chiara; Franciotta, Diego; Cortese, Andrea; Callegari, Ilaria; Serrati, Carlo; Mancardi, Gian Luigi; Schenone, Angelo; Leonardi, Alessandro; Benedetti, Luana
Abstract : View Supplementary Video 1